2020
DOI: 10.2196/15562
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude at Work: Prospective Cohort Study of a Web-Based, Single-Exposure Well-Being Intervention for Health Care Workers

Abstract: Background Emotional exhaustion (EE) in health care workers is common and consequentially linked to lower quality of care. Effective interventions to address EE are urgently needed. Objective This randomized single-exposure trial examined the efficacy of a gratitude letter–writing intervention for improving health care workers’ well-being. Methods A total of 1575 health care workers were randomly assigned to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 50 publications
(59 reference statements)
2
36
0
4
Order By: Relevance
“…Conversely, individual-focused interventions may carry the benefits of rapid deployment and adoption with minimal resource expenditure, and many are conducive to remote engagement using smartphones or other technology—features that may be particularly beneficial during the highly dynamic and taxing environment of a pandemic response. We have found that simple, bite-sized strategies are favorably received by HCWs, and have developed a family of these interventions for healthcare workers ( www.hsq.dukehealth.org/tools ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, individual-focused interventions may carry the benefits of rapid deployment and adoption with minimal resource expenditure, and many are conducive to remote engagement using smartphones or other technology—features that may be particularly beneficial during the highly dynamic and taxing environment of a pandemic response. We have found that simple, bite-sized strategies are favorably received by HCWs, and have developed a family of these interventions for healthcare workers ( www.hsq.dukehealth.org/tools ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated burnout with a widely used [ 9 , 19 , 29 32 ] 5-item emotional exhaustion scale shown to have excellent psychometric properties [ 19 , 29 , 32 – 34 ], external validity [ 9 , 31 , 33 ], and responsiveness to interventions [ 19 , 32 , 34 ]. To limit response burden, particularly during the pandemic, we elected to forgo assessment, of depersonalization and personal accomplishment to reduce survey burden.…”
Section: Methodsmentioning
confidence: 99%
“…The survey includes a 5-item derivative of the Maslach Burnout Inventory emotional exhaustion domain (henceforth burnout ). 29 , 30 , 31 , 32 , 33 , 34 While the Maslach Burnout Inventory is the gold standard for burnout measurement, a meta-analysis found that the other 2 domains of burnout, depersonalization and personal accomplishment, consistently produced smaller coefficient α estimates than emotional exhaustion. 35 In addition, emotional exhaustion is more psychometrically robust in discriminating between burnout and nonburnout outpatients suffering from work-related neurasthenia.…”
Section: Methodsmentioning
confidence: 99%
“…This difference in mean (SD) WLI scores persisted for the subgroup of single mothers (44 [22] vs 51 [22] for other single women; mean difference, −7 [−0.3 SDs]; P = .02) but not of single fathers (50 [28] vs 52 [25] for other single men; mean difference, −2 [−0.1 SDs]; P = .54).…”
Section: Univariate Analysismentioning
confidence: 97%